Servicio automatizado para elegir la modalidad de selección de un contratista para entes territoriales de sexta categoría - SAC (2022)
The system will allow the user (person designated for the elaboration of state contracts) to enter a series of parameters, which will indicate the modality of selection of a state contractor, after this the system will display the fields that must be filled out to download the template of the contract